AlGaN photodetectors for the UV‐C spectral region on planar and epitaxial laterally overgrown AlN/sapphire templates. Issue 3 (21st December 2012) - Knigge, A.; Brendel, M.; Brunner, F.; Einfeldt, S.; Knauer, A.; Kueller, V.; Weyers, M.; Toropov, Alexey; Ivanov, Sergey
Abstract We present Schottky type metal semiconductor metal (MSM) AlGaN photodetectors (PDs) suited for the ultraviolet C (UV‐C) spectral region grown on conventional planar AlN templates in comparison with epitaxial laterally overgrown (ELO) AlN templates. On planar templates solar blind MSM PDs with state‐of‐the‐art dark current in the pA range and a power independent responsivity are obtained. Using ELO templates with sapphire substrates tilted to the m direction the defect density in the absorber material is reduced compared to that for planar templates. The MSM PDs on this ELO templates exhibit photoconductive gain leading to external quantum efficiencies of up to 77 at 30 V applied bias surpassing that of the planar grown PDs by a factor of 100. In spite of the high gain these PDs also show low dark currents in the pA range up to 100 V applied bias, short switching times and two operating regimes with power independent responsivity. (© 2012 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)